(untitled) (Periphērica, 2023)
The ilustrado Filipino members of the Propaganda Movement at the end of the 19th century organized a large-scale campaign to demand administrative, economic, cultural, and social reforms from the Spanish colonial government. In their writings, through their newspaper La Solidaridad and other publications, in speeches at banquets and other events, even in their private correspondence, they questioned their relationship with the metropolis: they considered that times had changed, and the needs of the Filipinos had evolved. That is why they demand, among other things, political enfranchisement, parliamentary representation, freedom of the press and the cessation of certain abuses in the overseas territories. They also called for solidarity among the different colonies, although they felt that Spain was treating Puerto Rico and Cuba more favorably.